Exploration of Anxiety in Elderly with Hypertension During Covid-19 Pandemic in Jetis Yogyakarta - Binoriang, Dinasti Pudang; Setyaningsih, Fillia Afiani (Universitas Aisyah Pringsewu, 2022)
Anxiety about the COVID-19 pandemic is the most common mental health problem, including among the elderly. One of the effects of anxiety on physical health during the COVID-19 pandemic is hypertension or high blood pressure, especially for the elderly with hypertension. Anxiety experienced by the elderly with hypertension has an impact on the behavior of the elderly toward the condition of their health, such as a reduced interest elderly to visit health services. The aims: Explore the anxiety in elderly with hypertension during a covid-19 pandemic. Research method: Using a qualitative phenomenological approach on 8 elderly with hypertension through in-depth interviews. Results of the study: Showing the anxiety of the elderly with hypertension during the Covid-19 pandemic includes the anxiety condition of the elderly with hypertension, coping anxiety of the elderly with hypertension, and family support for the elderly with hypertension. Conclusion: Anxiety felt by hypertensive elderly in this study included fear of using public transportation, worry to interact with others and the assumption that Covid-19 was a threat caused the comorbid. Coping that they used to control the anxiety are praying, taking a rest, doing a home activity, es and not thinking too much about covid-19. While the family support that they get is emotional support, informational support, instrumental support,t, and appreciation. Abstrak: Latar belakang : Kecemasan terhadap pandemi COVID-19 menjadi masalah kesehatan mental yang paling banyak dijumpai pada setiap orang termasuk di kalangan lanjut usia. Pengaruh dari kecemasan terhadap kesehatan fisik yang dirasakan di masa pandemi COVID-19 salah satunya adalah hipertensi atau tekanan darah tinggi terutama pada lansia hipertensi. Kecemasan yang dialami lansia hipertensi berdampak pada perilaku lansia terhadap kondisi kesehatan seperti berkurangnya minat lansia untuk berkunjung ke pelayanan kesehatan. Tujuan penelitian : mengeksplorasi kecemasan yang terjadi pada lansia dengan hipertensi di masa pandemi COVID-19. Metode penelitian : Menggunakan kualitatif dengan pendekatan fenomenologi yang dilakukan pada 8 lansia hipertensi melalui wawancara in-depth interview. Hasil penelitian : kecemasan lansia hipertensi di masa pandemi Covid-19 mencakup pengalaman awal lansia terdiagnosa hipertensi, perilaku lansia selama memiliki hipertensi, penularan covid-19 menurut lansia hipertensi, kecemasan lansia hipertensi, koping kecemasan lansia hipertensi, upaya lansia menjaga kesehatan dimasa pandemic, respon lansia setelah kasus covid-19 melandai dan dukungan keluarga terhadap lansia hipertensi. Kesimpulan : Kecemasan yang dirasakan oleh lansia hipertensi pada penelitian meliputi kecemasan yang muncul pada saat pandemi Covid-19, perasaan takut menggunakan transportasi umum, perasaan khawatir berinteraksi dengan orang lain dan anggapan bahwa Covid-19 merupakan ancaman bagi kesehatan.